Non-Hodgkin Lymphoma in Children with Primary Immunodeficiencies: Clinical Manifestations, Diagnosis, and Management, Belarusian Experience. (1st February 2015) - Fedorova, Alina; Sharapova, Svetlana; Mikhalevskaya, Taisia; Aleshkevich, Svetlana; Proleskovskaya, Inna; Stsegantseva, Maria; Belevtsev, Mikhail; Aleinikova, Olga
Abstract : Introduction . Non-Hodgkin lymphoma (NHL) is the most frequent malignancy associated with primary immune deficiency disease (PID). We aimed to present the clinical characteristics and outcomes of Belarusian children with PID who developed NHL. Procedure . We reviewed 16 patients with PID and NHL. Eight patients had combined PID: 5—Nijmegen breakage syndrome, 1—Bloom syndrome, 1—Wiskott-Aldrich syndrome, and 1—Х-linked lymphoproliferative syndrome. Results . In 75% cases PID was diagnosed simultaneously or after the NHL was confirmed. PID-associated NHL accounted for 5.7% of all NHL and was characterized by younger median age (6.3 versus 10.0 years, P < 0.05 ) and by prevalence of large-cell types (68.8% versus 24.5%, P < 0.001 ). Children with combined PID had median age of 1.3 years; 5 of them developed EBV-associated diffuse large B-cell lymphoma with lung involvement. Five of 6 patients with chromosomal breakage syndrome developed T-NHL. Six patients died of infections; two died after tumor progression; one child had early relapse; two died of second NHL and one of secondary hemophagocytic syndrome. Overall, 4 children are alive and disease-free after a follow-up from 1.4 to 5.7 years. Conclusions . PID needs to be diagnosed early. Individualized chemotherapy, comprehensive supportive treatment, and hematopoietic stem cell transplantation may improve survival of children with PID and NHL.